2014
DOI: 10.1007/s11250-014-0688-0
|View full text |Cite
|
Sign up to set email alerts
|

Different screening tests and milk somatic cell count for the prevalence of subclinical bovine mastitis in Bangladesh

Abstract: Identification of cows with subclinical mastitis (SCM) is an important tool for sustainable dairying and implementing effective mastitis control strategies. A total of 892 quarters milk samples from 228 lactating cows were screened by California mastitis test (CMT), White side test (WST), Surf field mastitis test (SFMT), and somatic cell count (SCC) to study the prevalence of bovine SCM in some selected areas of Bangladesh. Out of 228 cows, 148 (64.9%), 138 (60.5%), 132 (57.9%), and 164 (71.9%) were found posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
47
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 8 publications
3
47
1
1
Order By: Relevance
“…Another study conducted by Katsande et al, (2013) showed comparatively lower prevalence (16.3%) of SCM in Zimbabwe. Previous studies in different regions of Bangladesh reported that the prevalence of SCM based on California Mastitis Test (CMT) varies from 29% to 37.6% (Islam et al, 2011;Islam et al, 2010) and based on SCC was 55% (Hoque et al, 2015). However, comparative higher prevalence of SCM indicates lack of awareness about SCM and farmers are not adapted to use different screening tools to detect SCM in timely fashion and maintain the udder and teat hygiene.…”
Section: Discussionmentioning
confidence: 99%
“…Another study conducted by Katsande et al, (2013) showed comparatively lower prevalence (16.3%) of SCM in Zimbabwe. Previous studies in different regions of Bangladesh reported that the prevalence of SCM based on California Mastitis Test (CMT) varies from 29% to 37.6% (Islam et al, 2011;Islam et al, 2010) and based on SCC was 55% (Hoque et al, 2015). However, comparative higher prevalence of SCM indicates lack of awareness about SCM and farmers are not adapted to use different screening tools to detect SCM in timely fashion and maintain the udder and teat hygiene.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical mastitis includes gross abnormality in milk, physical abnormalities of udder and abnormality of cow with systemic involvement while subclinical mastitis does not produce visible effects on udder or milk quality but has important effects on milk composition, mainly an increase in somatic cell counts [23,24]). While it is easy to detect clinical mastitis (seeing clotted milk), subclinical mastitis can only be demonstrated using various tests such as California Mastitis Test (CMT), Whiteside test (WST), Surf field mastitis test (SFMT), sodium lauryl sulphate test (SLST), Microscopic Somatic Cell Count (MSCC) and Electrical Conductivity (EC) [25][26][27]. However, CMT has been recognized as a highly sensitive test to detect bovine subclinical mastitis [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…IMI may persist beyond the resolution of the clinical symptoms of CM, and sub-sequent RCM flare-ups may be observed 17 . Almost every dairy herd has cows with SCM 15 , and a variety of pathogens can establish chronic infections which may only occasionally manifest the clinical signs of mastitis 19 .…”
Section: Introductionmentioning
confidence: 99%
“…However, future studies should delve further into characterizing microbiome diversity with larger sample sizes and the inclusion of gut/rumen microbiome sampling in addition to the milk samples for direct testing of microbial transfer across this axis to confirm the shift of microbiome and associated functions.MethodsScreening for mastitis, and samplingDetails of the study population and collected samples are presented inSupplementary Table 1. The California Mastitis Test (CMT ® , Original Schalm reagent, ThechniVet, USA) was used to screen different states of mastitis (clinical mastitis, CM; recurrent clinical mastitis, RCM; subclinical mastitis, SCM)19 . Cows with CM (mild, moderate, and severe) typically have abnormalities in the milk such as clots and flakes, swelled, red and hard mammary gland or systemic illness.…”
mentioning
confidence: 99%
See 1 more Smart Citation